Tirso de Molina, La prudencia en la mujer. Critical text of the princeps edition in Parte Tercera de las comedias del Maestro Tirso de Molina, 1634. Introduction and notes by Alice Huntington Bushee and Lorna Lavery Stafford. México, 1948. lii + 172 págs. / I. L. McClelland, Tirso de Molina. Studies in dramatic realism. Liverpool, 1948. 256 págs. (Liverpool Studies in Spanish Literature. Third Series). / Tirso de Molina, La villana de Vallescas, edited, with introduction, notes and vocabulary by Sherman W. Brown. D. C. Heath & Co., Boston, 1948. xxxiv + 238 págs. - Bruerton, Courtney (El Colegio de México, 1949)
Se reseñaron: Tirso de Molina, La prudencia en la mujer. Critical text of the princeps edition in Parte Tercera de las comedias del Maestro Tirso de Molina, 1634. Introduction and notes by Alice Huntington Bushee and Lorna Lavery Stafford; I. L. McClelland, Tirso de Molina. Studies in dramatic realism; y Tirso de Molina, La villana de Vallescas, edited, with introduction, notes and vocabulary by Sherman W. Brown.